2018
DOI: 10.1002/jhet.3409
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New Ibuprofen‐1,3,4‐oxadiazole‐1,2,3‐triazole Hybrids

Abstract: A new hybrid polydentate template comprising distinctive pharmacophoric groups, namely, ibuprofen, 1,3,4‐oxadiazole, and 1,2,3‐triazole linked through a thioether bridge was achieved by one‐pot synthesis by exploring multicomponent Cu‐catalyzed “click chemistry” approach. The target structures were characterized by NMR, IR, and LC‐Mass. The X‐ray analysis of 2‐(1‐(4‐isobutylphenyl)ethyl)‐5‐(((1‐(3‐nitrophenyl)‐1H‐1,2,3‐triazol‐4‐yl)methyl)thio)‐1,3,4‐oxadiazole (8a) confirmed the assigned structure. The in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…Hence, we designed and synthesized PDCP as shown in Scheme . Monomer 1 was synthesized with two 1,2 3-triazoles and two primary amines to improve the water solubility and afford potential antibacterial activity. , Tris­(4-bromophenyl)­amine was modified with borate as monomer 2 to offer multivalent junction sites for obtaining hydrophobic skeleton scaffolds. After being modified, the two monomers were conjugated via a palladium-catalyzed Suzuki coupling reaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Hence, we designed and synthesized PDCP as shown in Scheme . Monomer 1 was synthesized with two 1,2 3-triazoles and two primary amines to improve the water solubility and afford potential antibacterial activity. , Tris­(4-bromophenyl)­amine was modified with borate as monomer 2 to offer multivalent junction sites for obtaining hydrophobic skeleton scaffolds. After being modified, the two monomers were conjugated via a palladium-catalyzed Suzuki coupling reaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…1,2,3‐triazole is ubiquitous in numerous biologically active molecules and pharmaceuticals as triazoles are believed to be stable against metabolic degradation because of its structural and electronic similarity. On the other hand, 1,3,4‐oxadiazole ring is reported to improve ligand binding, flexibility, polarity, pharmacokinetics, in vivo metabolic profile, and aids in the design of molecules for the generation of newer derivatives that makes better interaction with receptors . Worthy to mention here that 1,3,4‐oxadiazole based anticancer drug, Zibotentan, is in late clinical trials, whereas, letrozole and anastrozole are triazole based drugs targeting aromatase that are used to treat breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds, mainly Di-Fluorophenyl (4g) and Naphthalene (4d), showed relatively acceptable antibacterial effects against Gram-Negative P. aeruginosa. In a study conducted by Rayam et al, it was reported that the antibacterial activity of new synthesis compounds revealed 2-(1-(4-isobutylphenyl)ethyl)-5-(((1-phenyl-1H-1,2,3triazol-4-yl)methyl)thio)-1,3,4-oxadiazole (8b) and demonstrated more potent antibacterial activity against E. coli and P. aeruginosa (19). In another study, Chortani et al showed how synthesis of novel 1, 3, 4-oxadiazole linked benzopyrimidinones conjugates.…”
Section: Discussionmentioning
confidence: 99%